Awareness Regarding Hepatocellular Carcinoma Risk in HCV Pa- tients Post-SVR: Which Subpopulation is more at Risk? - Fizza khalid (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Over the past three decades, the prevalence of hepatitis C virus (HCV) in Pakistan has remained persistently high, with no signs of decline1. Despite collaborative efforts to combat this viral epidemic, the shadow of HCV continues to loom large over our population. In the past few years, the only available treatment was interferon-based combination therapy, which demonstrated significantly high failure rates across various genotypes of HCV and induced severe side effects2. But over time, driven by emerging needs, significant advancements were made in HCV treatment leading to the advent of Di- rectacting Antivirals (DAAs). These medications have revolutionized HCV therapy with their in- creased therapeutic efficacy in targeting different genotypes of HCV, leading to a sustained virologic response (SVR) in over 90 percent of patients2,3. Sustained virologic response represents a mile- stone for individuals battling HCV, suggesting a successful eradication of the virus from their systems.